Domain-driven innovation: principles and practice - Meersman, Davor (Curtin University, 2013)
This thesis presents the research and development of a framework for Domain-Driven Innovation, defined as knowledge-based collaborative innovation by actors in a domain on the basis of a shared domain model for reasoning, knowledge discovery, communication, and information sharing. The thesis followed a hybrid Action Research / Design Science Research methodology and traverses 4 industry domains: real estate CRM, scuba diving equipment, online travel, and ambient assisted living.